Psychological Assessment in South Africa : Research and applications - Cockcroft, Kate; Laher, Sumaya (Book collections on Project MUSE., 2013)
This book provides an overview of the research related to psychological assessment across South Africa. The thirty-six chapters provide a combination of psychometric theory and practical assessment applications in order to combine the currently disparate research that has been conducted locally in this field. Existing South African texts on psychological assessment are predominantly academic textbooks that explain psychometric theory and provide brief descriptions of a few testing instruments. Psychological Assessment in South Africa provides in-depth coverage of a range of areas within the broad field of psychological assessment, including research conducted with various psychological instruments. The chapters critically interrogate the current Eurocentric and Western cultural hegemonic practices that dominate the field of psychological assessment. The book therefore has the potential to function both as an academic text for graduate students, as well as a specialist resource for professionals, including psychologists, psychometrists, remedial teachers and human resource practitioners.